Empagliflozin Alleviates Atherosclerosis Progression by Inhibiting Inflammation and Sympathetic Activity in a Normoglycemic Mouse Model - Liu Y; Wu M; Xu B; Kang L (Dove Medical Press, 2021)
Yihai Liu,1,2,* Mingyue Wu,1,* Biao Xu,1 Lina Kang1 1Department of Cardiology, Nanjing Drum Tower Hospital, Nanjing University Medical School, Nanjing, 210008, Jiangsu, People’s Republic of China; 2Department of Cardiology, Affiliated Drum Tower Hospital, Clinical College of Nanjing Medical University, Nanjing, 210008, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lina Kang; Biao XuDepartment of Cardiology, Affiliated Drum Tower Hospital, Nanjing University Medical School, Nanjing, 210008, Jiangsu, People’s Republic of ChinaEmail kanglina@njglyy.com; xubiao62@nju.edu.cnBackground: Recent clinical studies have revealed that sodium glucose co-transporter 2 inhibitors (SGLT2i) reduced cardiovascular events in type 2 diabetes. Here, we investigated whether empagliflozin, as a kind of SGLT2i, could alleviate atherosclerosis progression in non-diabetic mice.Methods: ApoE-/- mice were fed on a western diet for 12 weeks to induce atherosclerosis. The treatment group of mice was treated with drinking water containing empagliflozin (10mg/kg/day). On the 12th week, the whole aortas of each group were harvested. HE and Movat staining were performed for atherosclerotic lesion area and size. CD 68 and MCP-1 immunohistochemistry were used to evaluate inflammatory cell infiltration. Mouse serum lipid profiles (total cholesterol, triglyceride, low-density lipoprotein-C, and high-density lipoprotein-C), systemic inflammation level (IL-1β, IL-6 and IL-10), renin-angiotensin-aldosterone system (RAAS) and sympathetic activity (norepinephrine and neuropeptide Y) were measured by ELISA.Results: Empagliflozin could reduce the atherosclerotic lesion areas. Specifically, empagliflozin could significantly decreased inflammatory levels, RAAS and sympathetic activity in vivo. In vitro studies also showed that empagliflozin could inhibit IL-1β expression in oxLDL-treated macrophages by regulating NF-κB signaling.Conclusion: Empagliflozin could prevent atherosclerosis by repressing inflammation and sympathetic activity.Keywords: atherosclerosis, SGLT2i, empagliflozin, sympathetic activity, RAAS